AWAS BAHAYA PENYAKIT CVPD DAN TEKNIK PENGENDALIANNYA PADA TANAMAN JERUK - Wijaya, I. N.; Sritamin, M; Adiartayasa, W; Bagus, I. G. N; Sudarma, M; Puspawati, N. M. (Buletin Udayana Mengabdi; Vol 13 No 2 (2014): Vol 13, No. 2 (2014))
Education and training on integrated pest management of CVPD (Citrus Vein Phloem Degeneration) was held at Sengkaduan,Taro village, Gianyar regency on 14 August 2014. The activities aimed to improve the farmers’ knowledge of CVPD and integrated pest management. The training was attended by 44 participants from local farmer groups of Sengkaduan village. The method used were lectures, demonstration and practice in the citrus field. All participants participated enthusiastically and hope they have the next intensive training of the citrus culture. Keywords : Training, CVPD, Sengkaduan